Identifikasi Tekanan Darah Tinggi pada Warga Binaan Rumah Tahanan Kelas II B Masohi Tahun 2025 - Leiwakabessy, Jusuf; Huwae, Laura Bianca Sylvia; Tentua, Vebiyanti; Febriani, Reka; Bastian, Gustino Anjelo; Dyahnissa, Rahma; Rusmin, Rusdiah Marhumi (Pusat Riset dan Inovasi Nasional, 2026)
Blood pressure is the pressure exerted by blood pumped by the heart against the walls of the arteries. Abnormalities in blood pressure can take the form of high blood pressure or hypertension and low blood pressure or hypotension. Hypertension is a non-communicable disease that is one of the risk factors for cardiovascular disease, and sufferers often do not show any symptoms. This community service activity aimed to examine the results of blood pressure measurements among inmates at the Class IIB Detention Center in Masohi City. This study used a descriptive observational design with a cross-sectional approach. There were 95 inmates who participated in this activity. Data analysis was conducted using quantitative descriptive methods to describe the blood pressure measurement results based on demographic data such as age, gender, education level, occupation, height, and weight. The results showed that most respondents were in the 20-30 age range (44.2%) and male (91.6%). The level of education shows that most respondents only completed high school (54.7%) and the majority worked as farmers (30.5%). Anthropometric characteristics in terms of height show that most respondents were between 140-160 cm (47.4%) and weighed between 51-60 kg (43.2%). The distribution of blood pressure shows that most respondents are in the pre-hypertension (40%), normal (29.5%), grade 1 hypertension (17.9%), and grade 2 hypertension (10.5%). Therefore, routine blood pressure checks need to be carried out so that inmates in detention centers can avoid hypertension, which can be a risk factor for cardiovascular disease.